Correction - Sarsekova, Dani; Ayan, Sezgin; Abzhanov, Talgat (Hrvatski Sumarski Institut (Croatian Forest Research), 2021)
The authors wish to make the correction of the paper of Sarsekova et al. (2020). In the original paper, there was a mistake in the order of the first and the second name of the author Talghat Abbzhabnov. The correct order is Talghat Abbzhabnov.The original paper published on 11 May 2020 has been updated and both versions will be available on the paper webpage. The authors emphasize that this change does not affect the results of this research, and they apologize for any inconvenience this change may cause.
Keywords: Forestry; SD1-669.5